The Halo Effect in Business Risk Audits: Can Strategic Risk Assessment Bias Auditor Judgment about Accounting Details? - O'Donnell, Ed; Schultz, Joseph J. (The Accounting Review, 2005)
Many auditors use an audit methodology that requires a strategic risk assessment of their client's business model as a first step for assessing audit risks. This study examines whether the holistic perspective that auditors acquire in making a strategic risk assessment influences the extent to which they adjust account-level risk assessments when they encounter changes in accounts that are inconsistent with information about client operations. Based on halo theory from the performance evaluation literature, we hypothesize that auditors who (1) perform (do not perform) strategic assessment, and (2) develop favorable (unfavorable) strategic risk assessments, are less (more) likely to adjust account-level risk assessments for inconsistent fluctuations. Data from two laboratory experiments using experienced auditors support both hypotheses. Findings suggest that the halo effect generated during strategic assessment influences judgment by altering auditor tolerance for inconsistent fluctuations.